Micro analysis of the structure of the boiler pipe after experiencing the heating process and without heating - Mulia, Mulia; Suardi, Suardi; Susilo, Hendra (International Journal of Mechanical Computational and Manufacturing Research, 2023)
Piping is a tool that functions to drain fluid from one place to another. The problem at Factory X is the failure of the boiler pipe. Pipe failures that occur are known by indications of leaks in the boiler. The initial process of a failure in an ordinary pipe is characterized by corrosion. The problem of corrosion in boilers is usually caused by feed water or feed water which still contains high oxygen levels. The purpose of the research is to determine the microstructure of the boiler pipe after experiencing the combustion process in the combustion chamber. This research method is an analysis of the chemical composition of boiler pipe material, Visual / Macro and Micro Testing. From the results of the inspection, observation, it can be concluded, the cause of pipe damage on the outside of the fire side caused by erosion corrosion is classified as very severe because it is beyond the optimum thickness of the pipe. Specimen A which is a material that has not received heat treatment has a microstructure, where the condition of the fearlite area is greater than specimen B with heat treatment.